2004
DOI: 10.1111/j.1198-743x.2004.00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterisation of Helicobacter pylori isolates from an Argentinean adult population based on cag pathogenicity island right-end motifs, lspA-glmM polymorphism and iceA and vacA genotypes

Abstract: Isolates of Helicobacter pylori from 88 patients were characterised by cagA status, cagA pathogenicity island (PAI) right-end motifs, iceA, vacA and lspA-glmM genotypes, primarily by PCR-based analysis, to investigate whether Argentinean isolates differed from those recovered in southern Europe or other Latin American countries. PCR-based analysis of vacA alleles was confirmed by reverse hybridisation in 56 cases, while sequence analysis was performed either when iceA and vacA genotypes could not be determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
5
10
1
1
Order By: Relevance
“…Although located on a different loci of the H. pylori chromosome, cagA is strongly linked with VacA cytotoxic activity (Hocker & Hohenberger, 2003) and strains expressing the combination of these alleles and cag-PAI show enhanced epithelial cell injury (Ghiara et al, 1995). In our study, for patients with advanced gastric cancer, we found prevalent cagA positive (82.8%) and vacA s1m1 (70.7%) strains, corroborating the results of other studies (Miehlke et al, 2000;Leanza et al, 2004), and demonstrating that this combination can result in more virulent strains. These results are also similar to those obtained in China (Qiao et al, 2003), where H. pylori strains were cagA positive in 95% of samples in the gastric cancer group and the expression of type s1 vacA was more than type s2.…”
Section: Discussionsupporting
confidence: 92%
“…Although located on a different loci of the H. pylori chromosome, cagA is strongly linked with VacA cytotoxic activity (Hocker & Hohenberger, 2003) and strains expressing the combination of these alleles and cag-PAI show enhanced epithelial cell injury (Ghiara et al, 1995). In our study, for patients with advanced gastric cancer, we found prevalent cagA positive (82.8%) and vacA s1m1 (70.7%) strains, corroborating the results of other studies (Miehlke et al, 2000;Leanza et al, 2004), and demonstrating that this combination can result in more virulent strains. These results are also similar to those obtained in China (Qiao et al, 2003), where H. pylori strains were cagA positive in 95% of samples in the gastric cancer group and the expression of type s1 vacA was more than type s2.…”
Section: Discussionsupporting
confidence: 92%
“…An age- and sex-matched case-control study was conducted in only 1 report [47]. Although 46 articles showed a difference in the iceA type between gastritis and PUD, 14 articles did not show the distribution of GU and DU [12], [18][20], [24], [28], [32], [36], [39], [43], [48], [52], [53], [55]. Four studies examined the prevalence of iceA types in gastritis and GC, but not in PUD [13], [26], [44], [51].…”
Section: Resultsmentioning
confidence: 99%
“…We were interested to read the recent accounts in CMI regarding the distribution of Helicobacter pylori genotypes in Mexico and Argentina [1,2]. Epidemiological studies suggest that the prevalence of H. pylori infection varies between developed and developing countries, as well as according to ethnicity, place of birth and socioeconomic factors, even among people living in the same country.…”
mentioning
confidence: 99%